Evaluating Educational Concepts Mastery of Prospective Teachers in Ambon: An-ex-post-facto Study from Comprehensive Examination Result - Banawi, Anasufi; Syafit, Mohd.; Basta, Irawati; Ridwan, Muhammad; Sulaeman, Sulaeman (FKIP Universitas Lampung, 2022)
Evaluating Educational Concepts Mastery of Prospective Teachers in Ambon: An-ex-post-facto Study from Comprehensive Examination Result. Objectives: This study aims to describe prospective teachers’ education field comprehensive examination results. Methods: A descriptive ex-post-facto method is employed to obtain data from students who took the final project on three study programs (Islamic Education, Biology Education, and Mathematics Education) in one of Ambon’s Education Institutes of Education Personnel (LPTK/Lembaga Pendidikan Tenaga Kependidikan: Faculty of Tarbiyah and Teacher Training). Through observation and documentation, comprehensive examination scores of 108 students (27 males; 81 females) were obtained. Further, this data was analyzed using presentation techniques on six sub-components of the comprehensive educational exam. Findings: The results showed that the average ability of prospective teacher students was 83.94% (High category). Conclusions: Some prospective teachers were unable to adequately explain teacher competence and teaching theory. Therefore, they have to improve their capability in this topic. Keywords: learning outcomes, prospective teacher, comprehensive, education field.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202217